Les Najāḥides - Sobhi Bouderbala (Revue des Mondes Musulmans et de la Méditerranée)
This article examines the Najāḥid phenomenon, a dynasty of Ethiopian slaves that emerged on the political scene in Yemen at the end of the 4th/10th century, marked by the collapse of the Ziyādite state (whose capital was Zabīd, in the Tihāma) and the appearance of a multitude of autonomous powers, of which the most important was that of the Ṣulayḥids. The history of the Najāḥids in known thanks to the book al-Mufīd fī akhbār Zabīd, written by the founder of the dynasty, Jayyāsh b. Najāḥ, used by the Yemeni historian ‘Umāra in his al-Mufīd fī akhbār Ṣan‘ā’ wa Zabīd. The recruitment of slave soldiers allowed the installation of a military power in Zabīd whose command was vested in the qā'id, who bore the title of vizier as well. In this political model most likely inspired by models previously observed in Iraq and Egypt, regents, who bore the title of queen, the preceptor slaves supervised and educated the young Najāḥide emirs. In this system based on a regular supply of black slaves, especially among three Ethiopian jin-s, the Dahlak archipelago seems to have played a central role beginning in the middle of the 4th/10th century. The similarity observed between the Najāḥid and Dahlak sovereigns strongly supports the hypothesis of power wielded by former Ethiopian slaves in the archipelago, based, here too, on the central function of the qā’id.